Rapid regression of glioblastoma following carmustine wafer implantation: A case report - FUKAI, JUNYA (Mol Clin Oncol, 2016)
Carmustine wafers, which are locally delivered chemotherapy in the form of biodegradable implants, confer a survival benefit to patients with glioblastoma (GB) following surgical resection. While the adverse events of this method, including gas retention and perifocal edema, have been extensively investigated, the immediate efficacy of the implant has rarely been reported. To the best of our knowledge, this is the first reported case of GB in which the tumor rapidly regressed after partial surgical removal followed by implantation of carmustine wafers. A 77-year-old woman presented with motor aphasia and right hemiparesis. Neuroimaging revealed a tumor located in the left frontal lobe of the brain. The tumor was partially removed under 5-aminolevulinic acid fluorescence guidance and 8 carmustine wafers were implanted in the resection cavity. The histopathological findings suggested the diagnosis of GB. Genetic and immunohistochemical analyses revealed O(6)-methylguanine-DNA methyltransferase (MGMT) gene promoter methylation and low MGMT protein expression, respectively, in the tumor cells. One month after the operation, when adjuvant temozolomide chemotherapy was planned, computed tomography and magnetic resonance imaging revealed a marked regression of the residual tumor and perifocal edema. The patient's symptoms and signs had improved. As adjuvant temozolomide without radiation was therapeutically beneficial, the tumor gradually regressed and the patient has remained progression-free for >12 months after the operation. Therefore, adjuvant local chemotherapy with carmustine wafer implants was able to induce rapid regression of GB.